PEMBERIAN ARANG SEKAM PADI PADA MEDIA TANAM UNTUK MENDUKUNG PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) - Ida Nursanti; Hayata Hayata; Agus Jufriyanto (Nindikayla Institute, 2023)
Ultisol soil has very low nutrients and organic matter, so it is necessary to provide input of organic matter to support the supply of nutrients for the growth of cocoa plants. This study aims to determine the effect of several doses of rice husk charcoal on the growing media for cocoa seedling. This study used a completely randomized design (CRD) and treatment design, namely rice husk charcoal with 4 levels of composition including; S0 : 3,000 g of ultisol soil without rice husk charcoal, S1: 2,400 g of ultisol soil + 600 g of husk charcoal, S2: 2,250 g of ultisol soil + 750 g of husk charcoal, S3 : 2,100 g of ultisol charcoal + 900 g of husk charcoal. Data were analyzed using analysis of variance, followed by Duncan's Multiple Distance Test (DNMRT) at the level of 5%. The results showed that the application of rice husk charcoal to cocoa plants had a significant effect and produced plant height S2 (45.21 cm), stem diameter S2 (27.06 mm), root dry weight S2 (15.18 g), weight S2 canopy dryness (32.09 g) and S2 quality index (2.52).